Small effects of livestock grazing intensification on diversity, abundance, and composition in a dryland plant community. Issue 8 (25th July 2022) - Jordan, Samuel E.; Palmquist, Kyle A.; Burke, Ingrid C.; Lauenroth, William K.
Abstract: Livestock grazing is a globally important land use and has the potential to significantly influence plant community structure and ecosystem function, yet several critical knowledge gaps remain on the direction and magnitude of grazing impacts. Furthermore, much of our understanding of the long‐term effects on plant community composition and structure are based on grazer exclusion experiments, which explicitly avoid characterizing effects along grazing intensity gradients. We sampled big sagebrush plant communities using 68 plots located along grazing intensity gradients to determine how grazing intensity influences multiple aspects of plant community structure over time. This was accomplished by sampling plant communities at different distances from 17 artificial watering sources, using distance from water and cow dung density as proxies for grazing intensity at individual plots. Total vegetation cover and total grass cover were negatively related to grazing intensity, and cover of annual forbs, exotic cover, and exotic richness were positively related to grazing intensity. In contrast, species richness and composition, bunchgrass biomass, shrub density and size, percentage cover of bare ground, litter, and biological soil crusts did not vary along our grazing intensity gradients, in spite of our expectations to the contrary. Our results suggest that the effects of livestock grazing over multiple decades (mean = 46 years) in our sites are relatively small, especially for native perennial species, and that the big sagebrush plant communities we sampled are somewhat resistant to livestock grazing. Collectively, our findings are consistent with existing evidence that indicates the stability of the big sagebrush plant functional type composition under current grazing management regimes.